PWM‐Driven Thermally Tunable Silicon Microring Resonators: Design, Fabrication, and Characterization. Issue 9 (15th July 2019) - Pintus, Paolo; Hofbauer, Michael; Manganelli, Costanza L.; Fournier, Maryse; Gundavarapu, Sarat; Lemonnier, Olivier; Gambini, Fabrizio; Adelmini, Laetitia; Meinhart, Carl; Kopp, Christophe; Testa, Francesco; Zimmermann, Horst; et al.
Abstract: Ring resonators are one of the fundamental building blocks of advanced integrated optical circuits. They find applications as nonlinear optical elements, filters, sensors, and switches among others. Here, a comprehensive optimization framework and experimental results of thermally tunable microring resonators in silicon photonics is presented, with a focus on standard silicon photonic foundry processes. In order to minimize the total power consumption, the ring resonators are tuned by applying a pulse‐width‐modulated electrical signal to the heaters. The thermal performance of integrated silicon and metal heaters are investigated and compared using an effective model validated by the measurement results. The heater power consumption is minimized by optimizing heater cross section, resistance, and metal contact configurations. Using the multiproject wafer run developed at CEA‐LETI, it is demonstrated that a metal heater provides 30% lower power consumption compared to an integrated silicon one, reaching a power consumption of 27.53 mW per free spectral range. The measurements are in excellent agreement with the theoretically predicted thermal performance, with a deviation as low as 5%. The proposed framework, supported by the experimental results, will serve as a design guideline set that can be easily adapted for other thermo‐optic switches in future silicon photonic applications. Abstract : An opto‐electronic design framework to realize a low‐cost, power‐efficient, and ultrafast reconfigurable switching fabric based on thermally tunable standard silicon microrings is outlined. The work is a comprehensive theoretical and empirical performance analysis of various heater configurations of silicon microring heaters using commercially viable multiproject wafer run process and energy‐efficient pulse‐width‐modulation (PWM) electronics.